2011
DOI: 10.1002/dc.21741
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and subclassification of lymphomas and non‐neoplastic lesions involving mediastinal lymph nodes using endobronchial ultrasound‐guided transbronchial needle aspiration

Abstract: EBUS-TBNA is a minimally invasive procedure which provides sufficient sample for definitive primary diagnosis and classification of malignant lymphoma and granulomatous inflammation in patients with mediastinal lymphadenopathy. Rapid on-site specimen assessment is invaluable for appropriate assignment of sample to ancillary studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…During the procedure, the on-site cytology assessment guided the number of passes and the area in the lymph node to biopsy that yield the best quality specimen. This collaboration ensures that adequate specimens are acquired for both detailed morphologic assessment and ancillary testing required to subtype lymphomas [22]. Secondly, despite the wide adoption of fine needle aspiration as the diagnostic tool for lymphoma, societies including the European Society of Medical Oncologist [23] and the National Comprehensive Cancer Network [24] explicitly express preference for excisional biopsies at the time of initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…During the procedure, the on-site cytology assessment guided the number of passes and the area in the lymph node to biopsy that yield the best quality specimen. This collaboration ensures that adequate specimens are acquired for both detailed morphologic assessment and ancillary testing required to subtype lymphomas [22]. Secondly, despite the wide adoption of fine needle aspiration as the diagnostic tool for lymphoma, societies including the European Society of Medical Oncologist [23] and the National Comprehensive Cancer Network [24] explicitly express preference for excisional biopsies at the time of initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The development of endobronchial ultrasound (EBUS), which allows ultrasoundguided aspiration of mediastinal and pulmonary lymph nodes and masses (EBUS transbronchial needle aspiration [TBNA]), offers the opportunity to incorporate FNAC to the diagnosis and management of mediastinal lymphoid neoplasms, which had hitherto required sampling by more invasive techniques, such as mediastinoscopy, mediastinotomy, or surgical thoracoscopy. Although there is support for the use of EBUS-TBNA in lung cancer (9)(10)(11)(12) and in the evaluation of isolated mediastinal lymphadenopathy (13), there is limited information of its value in the diagnosis and management of lymphoma (14)(15)(16)(17)(18). The ability of FNAC in general (5) and EBUS-TBNA specifically (14,18) to correctly diagnose and subtype lymphoma has been questioned.…”
mentioning
confidence: 99%
“…[12] However, recent studies have demonstrated that diagnostic accuracy has significantly improved as a result rapid on-site pathological evaluation. [13] Chemotherapy (CHOP) is the standard treatment for lymphoma. Particularly in cases with cardiac or major vessel invasion, bulky lymphadenopathy (>10 cm), or a mass lesion with a diameter greater than one-third the transverse diameter of the chest, radiotherapy is typically combined with standard therapy.…”
Section: Discussionmentioning
confidence: 99%